2008
DOI: 10.1111/j.1600-079x.2008.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin receptor‐mediated protection against myocardial ischaemia/reperfusion injury: role of its anti‐adrenergic actions

Abstract: Melatonin has potent cardioprotective properties. These actions have been attributed to its free radical scavenging and anti-oxidant actions, but may also be receptor mediated. Melatonin also exerts powerful anti-adrenergic actions based on its effects on contractility of isolated papillary muscles. The aims of this study were to determine whether melatonin also has anti-adrenergic effects on the isolated perfused rat heart, to determine the mechanism thereof and to establish whether these actions contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 54 publications
5
75
0
1
Order By: Relevance
“…In addition, melatonin might decrease norepinephrine plasmatic levels, as previously described, 52 or it may have antiadrenergic effects through the choroid-melatonin receptor. 53 One of the limitations of this study is the relatively small number of patients; however, the prevalence of CSCR has been estimated as low as 5.8 per 100 000 population, with chronic CSCR reported to be as infrequent as 5% of those cases, making very difficult to obtain larger recruitment groups. Another limitation of this study is the difficulty in obtaining reliable data about previous episodes of the patient's disease as most of them cannot recall the prior events with precision.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In addition, melatonin might decrease norepinephrine plasmatic levels, as previously described, 52 or it may have antiadrenergic effects through the choroid-melatonin receptor. 53 One of the limitations of this study is the relatively small number of patients; however, the prevalence of CSCR has been estimated as low as 5.8 per 100 000 population, with chronic CSCR reported to be as infrequent as 5% of those cases, making very difficult to obtain larger recruitment groups. Another limitation of this study is the difficulty in obtaining reliable data about previous episodes of the patient's disease as most of them cannot recall the prior events with precision.…”
Section: Discussionmentioning
confidence: 90%
“…Five patients with chronic CSCR served as a control group. The mean age of control patients was 44 years old (range, [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], with the woman/man ratio being 1 : 4. The number of right and left eyes studied was also similar (3 right eyes and 2 left eyes).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its acute soporific, phase-shifting, and anti-hypertensive effects, melatonin has powerful cardioprotective benefits. This may be due in part to melatonin's properties as a potent anti-oxidant, but studies using a perfused rat heart system have demonstrated a possible receptor dependent protection against ischemia/reperfusion injury (Genade et al, 2008). Clinical trials are underway to test the effectiveness of melatonin in treating human patients with ischemic heart disease (Dominguez-Rodriguez, 2007;.…”
Section: Chronotherapeutic Interventionsmentioning
confidence: 99%
“…Male offspring rats at postnatal day 17 ± 1 weighing about 50 g were used. Obstructive jaundice was induced by opening a midline incision and ligating and dividing the common bile duct with double ligatures of the proximal duct as described previously (4).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…Melatonin, an endogenously produced indoleamine secreted by the pineal gland, has the ability to scavenge reactive oxygen species (ROS) and reactive nitrogen species (3). The direct free radical scavenging effect of melatonin is independent of receptors; however, melatonin-mediated protective effect has been attributed to its receptor-dependent effect on the nitric oxide (NO) pathway (4). l-Arginine, a substrate for NO synthase to generate NO, is mainly derived from protein catabolism (85%) or from lcitrulline by argininosuccinate synthase (ASS) and argininosuccinate lyase (ASL) (5).…”
mentioning
confidence: 99%